EFFECT OF WORK MOTIVATION, EMOTIONAL INTELLIGENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Yudi Siswadi; Dinda Lestari (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Performance as the level of efficiency of an activity is able to achieve the quantity and quality targets that have been set. Increasing employee performance itself will encourage increased performance and other factors of the entire performance of the entire business or company.The objectives of the research to be carried out are: to find out and analyze whether there is an influence of work motivation on employee performance at PT. Bank Sumut Medan Head Office. To find out and analyze whether there is an Effect of Emotional Intelligence on Employee Performance at PT. Bank Sumut Medan Head Office. To find out and analyze whether there is an Influence of Work Discipline on Employee Performance at PT. Bank Sumut Medan Head Office. To find out and analyze whether there is an Influence of Work Motivation, Emotional Intelligence, and Work Discipline on Employee Performance at PT. Bank Sumut Medan Head Office. This study uses an explanatory research approach. Determination of the number of samples taken as respondents using the Slovin formula. The data collection technique used in this research is to use a questionnaire. The data analysis technique in this study used multiple regression, classical assumptions, hypothesis testing and coefficient of determination with the help of the SPSS for Windows Version 22 program. Based on the results of the study there was a significant effect of work motivation on employee performance at PT. Bank Sumut Medan Head Office. There is a significant influence of Emotional Intelligence on Employee Performance at PT. Bank Sumut Medan Head Office. There is a significant influence of Work Discipline on Employee Performance at PT. Bank Sumut Medan Head Office. There is a significant influence of work motivation, emotional intelligence and work discipline on employee performance at PT. Bank Sumut Medan Head Office. The data analysis technique in this study used multiple regression, classical assumptions, hypothesis testing and coefficient of determination with the help of the SPSS for Windows Version 22 program. Based on the results of the study there was a significant effect of work motivation on employee performance at PT. Bank Sumut Medan Head Office.